Exploring Local Residents’ Psychological Stances for Regenerative Tourism - Ceniza, Rose Anelyn Visaya; Ceniza, Chris Lloyd Alderite; Liporada, Audrey Ann Tabigue (Journal of Psychological Perspective, 2025)
This study aimed to investigate the psychological stances of local residents on tourism development in the coastal area where beach resorts and other captivating sights were established. It intended to contribute evidence-based information for policy considerations and livelihood programs toward regenerative tourism. This study utilized a qualitative research design that employed a one-on-one interview and focus-group discussions to gather meaningful data. The research participants were the local residents including males and females, living within the tourism structures in the Municipality of Governor Generoso, Davao Oriental, Philippines. The findings show that residents expressed concern for safety alongside feelings of pride, joy, and gratitude toward tourism. These psychological stances reflect a growing sense of belonging and ownership, aligning with regenerative tourism’s emphasis on community agency and emotional investment. This was further reflected in their active participation in community initiatives and efforts to protect and promote their local environment. On the other hand, some participants manifested an anxious mentality and emotionality of repression and inhibition despite the growing tourism industry in their place. Despite the economic advancements brought by tourism, certain individuals continued to experience feeling of anxiety and emotional constraint, hindering their full participation in the industry’s benefit. Based on the psychological stances of local residents on tourism development, policy recommendations were discussed and a capacity-building program was designed and proposed. This program aims to support regenerative tourism, ultimately enhancing the quality of life of the people in the community. Additionally, the socio-demographic profiles of the participants were described.